2013
DOI: 10.1002/14651858.cd006823.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Wound drainage after axillary dissection for carcinoma of the breast

Abstract: There is limited quality evidence that insertion of a drain following axillary lymphadenectomy reduced the odds of developing a seroma and reduced the number of post-operative seroma aspirations. These benefits should be balanced against an increased length of hospital stay in the drained population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 26 publications
3
43
3
3
Order By: Relevance
“…It has been suggested that suction drainage markedly decreased the development of postsurgical seroma (10). Furthermore, it has been reported that nearly all of the total seroma formation was drained within the 48 hours of the post-operative period (1,9). Interestingly, the levels of seroma showed wide variation between the trials.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that suction drainage markedly decreased the development of postsurgical seroma (10). Furthermore, it has been reported that nearly all of the total seroma formation was drained within the 48 hours of the post-operative period (1,9). Interestingly, the levels of seroma showed wide variation between the trials.…”
Section: Discussionmentioning
confidence: 99%
“…Axillary dissection is related to the formation of postoperative seroma (33). The development of a seroma has been reported in 10% to 52% of cases (9,34). If a great number of lymph nodes were dissected from the axilla, much more seromas were observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations